2019
DOI: 10.1101/593194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of miniaturization effects and channel selection strategies for EEG sensor networks with application to auditory attention detection

Abstract: Objective:Concealable, miniaturized electroencephalo-graphy ('mini-EEG') recording devices are crucial enablers towards long-term ambulatory EEG monitoring. However, the resulting miniaturization limits the inter-electrode distance and the scalp area that can be covered by a single device. The concept of wireless EEG sensor networks (WESNs) attempts to overcome this limitation by placing a multitude of these mini-EEG devices at various scalp locations. We investigate whether optimizing the WESN topology can co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…They did not report optimal electrode positions. Narayanan and Bertrand (2019) also analyzed the channel subset selection problem in the context of auditory attention decoding, using a channel selection strategy based on the same utility metric discussed in the present study, but without imposing the symmetric grouping approach discussed in Section 2.2.5. They found that, on average, the decoding accuracy remained stable when using a number of channels greater or equal to 10.…”
Section: Discussionmentioning
confidence: 99%
“…They did not report optimal electrode positions. Narayanan and Bertrand (2019) also analyzed the channel subset selection problem in the context of auditory attention decoding, using a channel selection strategy based on the same utility metric discussed in the present study, but without imposing the symmetric grouping approach discussed in Section 2.2.5. They found that, on average, the decoding accuracy remained stable when using a number of channels greater or equal to 10.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) ) would improve. For each 120 s trial, we found the mean and standard deviation of the TRF of the channel ‘Tp7’ (one of the channels resulting in high AAD performance as shown in Narayanan and Bertrand (2019) ), across trials, as shown in Fig. 9 .…”
Section: Validation Experimentsmentioning
confidence: 99%
“…To gain a better understanding of the denoising ability of our approach, we estimated short-term TRFs (as in section III-B) for the attended and unattended stimuli on 120 s trials, from the raw EEG as well as the SI-GEVD filtered EEG this time projected back to the electrode space and investigated whether attention decoding from the TRFs directly (as in Akram et al (2017)) would improve. For each 120 s trial, we found the mean and standard deviation of the TRF of the channel 'Tp7' (one of the channels resulting in high AAD performance as shown in Narayanan and Bertrand (2019)), across trials, as shown in figure 9.…”
Section: Auditory Attention Decodingmentioning
confidence: 99%